ESTETIKA MASKULIN DAN EKSKLUSI PEREMPUAN DALAM FILM EKO-KRITIK SEORANG KAMBING (2016) - Ratna Noviani (Jurnal Kawistara, 2019)
The eco-critical film, Seorang Kambing (Tunggung Banjaransari, 2016), is part of eco-cinema, which mainly talks about problems of water crisis throughout its narrative. Eco-cinema has not only audio-visual presentations regarding environmental issues, but also functionalizes aesthetic choices, which could encourage viewers to have mindful and critical awareness of ecological problems. This article is aimed to examine how the film narrative of Seorang Kambing reproduces gender problems around the issue of water crisis. This article uses Stella Bruzzi’s (2013) concept of masculine aethetics in the cinema and the approach of eco-feminism, which critically reveals the connections between the oppressions of the nature and those toward women. By applying narrative analysis, which is presented by Helen Fulton (2005), this article reveals that masculine aethetics are functionalized predominantly in the film to narrate the problems of water crisis. Paradoxically, Seorang Kambing, as an intended eco-critical film, seems to simply overlook the significant roles of women around the issue of water crisis. In addition, the film reproduces the exclusion of women from the discourse of water crisis.